Russian banks' private deposit interest rates and market discipline - A.A. Peresetsky; A.M. Karminsky; S.V. Golovan (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
This paper examines the extent to which the observed diversity of private deposit interest rates in Russia is explained by bank financial indicators.We also test for whether the introduction of the bank deposit insurance scheme in 2005 affected deposit interest rates.Our results suggest market discipline in the Russian banking system involves Russian depositors demanding higher deposit interest rates from banks with risky financial policies.This discipline seems stronger than in developed countries.Our study suggests also that the risks taken by banks increased after introducing the deposit insurance.
URN:NBN:fi:bof-201408072178
Keywords: D43; E53; G21; P34; 330; banking; deposit interest rates; moral hazard; deposit insurance; Russia